PENGARUH GOOD CORPORATE GOVERNANCE DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA (STUDI PADA PERUSAHAAN YANG TERGABUNG DALAM INDEKS KOMPAS 2010-2012) - Totok Rudianto (Program Magister Akuntansi Unsyiah, 2014)
ABSTRACT This research aimed to investigate the influence of composition independent commissioner,independent audit committee, institutional ownership, managerial ownership quality audit to earnings manage2010 -2012. It used 300 companies. This research used a cencus menthod, the analysis conducted in this research was multiple regression analysis. The result of the research show that simultaneously composition of independent commissioner, independent audit committe, institutional ownership, managerial ownership, audit quality influenced to earnings management. Meanwhile, partially only quality audit influenced to earnings management. The variable composition of independent commissioner, independent audit committe, institutional ownership and managerial ownership didnot influence to earnings management. For the following research, it is recommended to add several veariabels such as competency board of directors, competency board of commissioner, and gender of board of commissioner. Keywords: earnings management, composition independent commissioner, independent audit committe, institutional ownership, managerial ownership and quality audit.